The dream of a pure community: Woodstock's counter-memory, 1882–1913 - Alfred, Luke Martyn (Unknown, 2017)
One of the governing assumptions of this thesis is that there is a distinct form of historiographic endeavour called a genealogy. The genealogy is not merely a polemical critique of orthodox historiography, but also functions as a working methodology. It is thus capable of reaching significant conclusions. This thesis is an attempt to practice a genealogy of the Woodstock Municipality from 1882, the year of its inception, to 1913, the year in which it became a part of the greater Cape Town Municipality. I have chosen this period because I believe it demonstrates in sometimes-dramatic form, the unique difficulties facing a growing administrative apparatus. Furthermore, the Woodstock Municipality was an administrative invention, which was congruent with a new form or economy of power. This form of power was above all concerned with a type of administration which facilitated discreetly the gentle growth of a market economy in the Colony. It was also concerned to "govern" and discipline the rapidly growing population in a cost-effective, unobtrusive and intelligent way. My analysis of this new economy of power suggests the following: if we attempt to render intelligible the emergence of several institutions (or regimes of discipline within longstanding structures) that were contemporary with the period under investigation, we might find that this new form of power took hold at the institutional level. Correlatively, we might also find significant differences being enacted at the level of disciplinary practice. One of the further advantages of an institutional analysis is that it will allow us to historicise objects (like the human body), isolate discursive practices (moral languages of "responsibility"), and analyse forms of knowledge (the emergence of medical knowledge about the population), within the context of a "different" methodology. We will thus be posing a polemical threat to those who believe that the body has no history; that language is reducible to the intention of a centered subject; and that knowledge "evolves" in conjunction with a continuous, teleological rationality.